ENHANCED LIPASE PRODUCTION FROM CELOSIA ARGENTEA SEED OIL USING MUTANT BACILLUS PUMILUS UVM6 - P. SATHIYA; K. DHANDAYUTHAPANI (The Journal of Research ANGRAU, 2024)
A mutant strain was developed by random mutation using UV-C radiation from wild parent  strain Bacillus pumilus KMAS7. Following mutagenesis, eleven bacterial isolates were used for maximum lipase production and found that the strain UVM6 produced high lipase of 36.46±0.05 UmL-1 from C. argentea seed oil. It was 1.38 times more abundant than the wild parent strain. Robust mutant strain UVM6 was selected and designated as B. pumilus UVM6. Then this mutant strain was cultivated in SmF for production of lipase using C. argentea seed oil under different nutritional sources. An overall 2.95-fold enhanced extracellular lipase production (62.42±0.03 UmL-1) was obtained from C. argentea seed oil by SmF using 4% v/v C. argentea seed oil, 0.5% w/v glucose, 1% w/v ammonium sulphate and 10 μML-1 Zn as inducer, carbon, nitrogen and trace element sources respectively. Seed oil of C. argentea has been used in traditional folk medicine, but this is the first time we’re reporting lipase production from C. argentea by the newly isolated mutant B. pumilus UVM6.